The Impact of Yogurt Enrichment with Millet Milk and Orange Peel Powder: Life Sciences-Nutrition and Dietetics - S. Nair, Sandra.; Peerkhan, Nazni (International Journal of Life Science and Pharma Research, 2022)
In recent years, the development of enriched dairy products with fruits or fruit parts has been growing due to their potential health benefits and consumer preferences. Orange peel is a beneficial source of antioxidants and dietary fiber. People are becoming more conscious of functional essential ingredients in the current lifestyle circumstances, which is driving up demand for functional foods. A significant drought-resistant crop, millet is a nutritionally staple meal throughout Africa and Asia. Additionally, millet is a rich source of bioactive substances that have antioxidant properties. Antioxidants must be consumed through diet if human health is to be improved. This research aimed to evaluate developed yogurt’s physiochemical, total phenolic, and total flavonoid content, antioxidant activity, and organoleptic properties. They used cow’s milk, barnyard millet milk, and orange peel powder (0.5, 1, 1.5 percent) that had been refrigerated at 4ºC for 28 days. As the storage period extended, the pH values of all groups declined, with an increase in titratable acidity. OPP1 (Orange Peel Powder) had a high viscosity, but in the syneresis test, it had the lowest value among the enriched yogurt samples. The cell count and pH value of L.bulgaricus and S.thermophilus decreased after storage, whereas titratable acidity increased. Various methods were used to determine the antioxidant capacity. The antioxidant activity increased in proportion to the quality of the orange peel powder used. Sensory analysis data suggested that among the fortified yogurts, OPP1 0.5% orange peel powder) had the highest overall value during the storage period. As the storage period increased, the organoleptic value decreased. These findings indicate that yogurt fortified with cow’s milk, barnyard millet milk, and orange peel powder (0.5, 1, 1.5 percent) has higher quality and antioxidant activity than the control.